Preliminary Study on the Perception of Engineering Students on Metaverse - Sidhu M.S.; Lee C.K.; Hassan Z.; Mousakhani S.; Sidhu K.K.; Anuar A. (Institute of Electrical and Electronics Engineers Inc., 2025)
Understanding Mechanics Dynamics is a crucial foundation in engineering education. Nonetheless, many engineering students face challenges in this course, leading to a notable rate of academic setbacks. The difficulties encountered often stem from issues such as struggling to visualize static images, dealing with complex engineering models, and misinterpreting pivotal concepts. This paper examines into preliminary research investigating how students perceive the Metaverse as a potential solution to overcome these learning obstacles in Engineering Mechanics Dynamics at University Tenaga Nasional (UNITEN). The primary objective of our pilot study is to collect insights into the specific learning hurdles faced by students in the subject and to gauge their views on employing a constructivist learning approach through the Metaverse. To achieve this, we devised a questionnaire and administered it via an online platform to a cohort of 41 engineering students. The findings were analyzed using a descriptive statistics methodology. The preliminary results reveal that students are particularly concerned about visualization challenges, the complexity of the subject matter, the mathematical rigor involved, communication skills, and teamwork. Interestingly, despite a low awareness of the Metaverse approach, students express a positive attitude towards its potential implementation in their classrooms. Thus, a further investigation on Metaverse needs to be conducted as to aid students in enhancing their learning experience. ? 2024 IEEE.